Soucis de la littérature - Opmærksom læsning, med og uden teori - Jørgensen, Steen Bille (Passage - Tidsskrift for litteratur og kritik, 2012)
Steen Bille Jørgensen: “Soucis de la littérature. Attentive Reading, With and Without Theory” This article examines in what ways contemporary French theory is characterized by a valorization of the literary as such. Though certain critics (like Antoine Compagnon) tend to regret the ambitious theoretical constructions of the sixties and seventies, the current emphasis on stylistics reveals a renewed concern for the literary work. This souci deliberately neglects abstract speculation in favor of more individual, less ideological, approaches to literature. Thus, one of the main contributions of French theory from the last 25 years is a focus on the existential – or anthropological – aspect of literature. Through readings of a series of critics, the article argues that the (phenomenological) notion of événementialité is central in literature’s capacity to involve the actual reader. The proposed reading of the Danish writer Kaalø is meant to show how this particular reader responds to its combined formal and existential concerns. This is ultimately a question of rhythm; formal rhythm and existential rhythm.